2016
DOI: 10.1016/j.cl.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Software Product Lines Engineering in the development of external DSLs: A systematic literature review

Abstract: The use of domain-specific languages (DSLs) has become a successful technique in the development of complex systems. Consequently, nowadays we can find a large variety of DSLs for diverse purposes. However, not all these DSLs are completely different; many of them share certain commonalities coming from similar modeling patternssuch as state machines or petri netsused for several purposes. In this scenario, the challenge for language designers is to take advantage of the commonalities existing among similar DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…To this effect, all models that are conform to a language defined by a set of selected features, are still valid models of a language that is based on these features and arbitrary other additional selected features. Through a systematic literature review [20] comparing different approaches for LPLs, the authors identified 14 approaches realizing LPLs, where many different concepts are involved. Some of the approaches support variability in abstract syntax only [10,23,29].…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…To this effect, all models that are conform to a language defined by a set of selected features, are still valid models of a language that is based on these features and arbitrary other additional selected features. Through a systematic literature review [20] comparing different approaches for LPLs, the authors identified 14 approaches realizing LPLs, where many different concepts are involved. Some of the approaches support variability in abstract syntax only [10,23,29].…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…A recent advance in SLE is the notion of language product lines [8,9] . In analogy with software product lines [35] , a language product line is a product line where the products are languages.…”
Section: Language Product Linesmentioning
confidence: 99%
“…Over the last decade, the Software Language Engineering (SLE) community has proposed various reuse techniques, mostly leveraging previous experiences in software reuse (e.g., aspects [2] , polymorphic [3] and parametric [4] reuse, composition operators [5,6] , language product lines [7][8][9] ). Although these techniques address a wide range of scenarios, the development of realistic languages is still difficult as it requires to combine them.…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to leverage previous engineering efforts to minimize implementation from scratch. To achieve such a challenge, the research community in software language engineering has proposed the use of Software Product Line Engineering (SPLE) in the construction of DSLs [13,14]. This led to the notion of Language Product Line Engineering (LPLE) -i.e., the construction of software product lines where the products are languages [12,15]-.…”
Section: Introductionmentioning
confidence: 99%